Mental health matters a cross-country analysis of mental health legislation experience and suicide rates - Abrenica, Katrielle Pauline C. (School of Economics, University of the Philippines Diliman, 2019)
With hundreds of thousands of lives lost due to suicide each year, governments have intervened via policies, programs and legislation geared towards suicide prevention and overall improved mental health. Using panel data obtained from 166 countries from the years 1990 to 2016, this study analyzes the effect of mental health legislation on suicide rates. It uses panel data methods to analyze the effects of a country_s years of experience with mental health law, as well as other control variables related to religion, substance use disorder prevalence, and economic conditions. The study shows that for countries that have passed mental health legislation, longer experience with a mental health law decreases suicide rates. However, the decrease in suicide rates diminishes from year to year. Moreover, the findings reveal that substance use disorder and unemployment have a positive relationship with suicide rates, while income per capita and religiosity have a negative relationship with suicide rates.